Wingate Anaerobic Testing with a Modified Electromagnetically Braked Elliptical Trainer. Part II: Physiological Considerations - Ozkaya, Ozgur; Colakoglu, Muzaffer; Fowler, Dianne; Kuzucu, O. Erinc; Colakoglu, Sule (IOS Press, 2009)
The Wingate Anaerobic Test is the most common method used to evaluate explosive power and anaerobic capacity. The Wingate Anaerobic Test performed on an elliptical trainer (WAnTet) may be more accurate than the Wingate Anaerobic Test performed on a cycle ergometer (WAnTc) since larger muscle group recruitment with the WAnTet results in higher anaerobic output. The purpose of this study was to evaluate and compare peak power ( PP), average power (AP), fatigue index (FI%) and delta lactate responses (Delta La) between WAnTet and WAnTc in healthy male university athletes. In our test subjects, (n = 40; 21 +/- 2 years old), PP ( 1463 +/- 238 vs. 879 +/- 162 watts) and AP ( 1127 +/- 191 vs. 649 +/- 82 watts) for the WAnTet were higher when compared to the WAnTc ( p < 0.001). FI%s of WAnTet and WAnTc were similar ( 49.8 +/- 10.3% and 46.9 +/- 8.3%, respectively; p = 0.054) but. La values were higher for WAnTet than for WAnTc (12.9 +/- 1.7 mM vs. 9.2 +/- 1.5 mM, respectively; p < 0.001). Using an elliptical trainer, rather than a traditional cycle ergometer, results in a more accurate measure of anaerobic power when Wingate Anaerobic Testing is performed.
Ozkaya, Ozgur/0000-0003-4222-5761
Keywords: Wingate Anaerobic Test; Elliptical Trainer; Cycle Ergometer